Study on the Method of Automatically Drawing Multiscale Engineering Geotechnical (Geological) Sections Step by Step of Engineering Layers including Lenses - Guangjun Ji; Nannan Zhao; Xiaoyuan Zhou; Qian Wang; Yan Lu; Zizhao Cai (Advances in Civil Engineering)
Drawing the engineering sections automatically and efficiently is significant for the investigation results of geotechnical engineering to provide the scientific and detailed geological basis for urban planning and construction, but it is still difficult to draw the engineering geological sections automatically without manual edit. A method, taking the engineering strata in Quaternary loose sedimentary as the research object, was proposed to automatically draw multiscale engineering geological sections of engineering layers including lenses and strata pinch-out based on the investigation results and borehole data of geotechnical (geological) engineering. Firstly, the spatial information of the top and bottom boundaries of any borehole layer were extracted, and then based on the stratigraphical column, the borehole layer was studied by a step-by-step coarsen from the finest stratigraphical column to the coarsest stratigraphical column, and the occupation relationship among layers was distinguished; secondly, from the coarsest stratigraphical column to the finest level stratigraphical column step-by-step and taking the radial basis function (RBF) interpolation as an example, top and bottom boundaries were interpolated, respectively, by following the order of current stratigraphical column; next, topological relationship among engineering layers was processed according to contact relationship of strata, and strata boundaries with 0 thickness were deleted; and finally, auxiliary information such as scaler and legend were added in section to complete the drawing of multiscale sections. Studies of one site case and one region case demonstrate that the method can perfectly and automatically draw the engineering geological section of engineering layers including lenses and strata pinch-out.